Hubungan Pengambilan Keputusan dan Iklim Organisasi terhadap Kinerja Guru Madrasah Tsanawiyah di Kabupaten Tangerang - Wijiyono Wijiyono (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
The purpose of this study was to find efforts to improve teacher’s performance, namely decision making, and organizational climate, both individually and jointly. This research used sequential explanatory. The population of this study was 669 Private Madrasah teachers in Tangerang regency, with a sample of 251 teachers made proportional random sampling. Data were collected by questionnaires and statistical analysis were used regression correlation. Results of this study indicated that: (1) there is positive correlation between decision making with teacher performance, with correlation coefficients ry1=0,488 (p<0,01), (2) there is positive correlation between organizational climate with teacher performance, ry2=0,378 (p<0,01),(3) there is positive correlation between decision making, organizational climate together with teacher performance, correlation coefficients ry12=0,779 (p<0,01). This result shows that teacher’s performance can be improved through development of decision making, and organizational climate, both individually and jointly.